Diagnostic performance of whole-body SPECT/CT in bone metastasis detection using 99mTc-labelled diphosphate: a systematic review and meta-analysis. Issue 12 (December 2020) - Alqahtani, M.M.; Fulton, R.; Constable, C.; Willowson, K.P.; Kench, P.L.
Abstract : AIM: To evaluate the diagnostic performance of whole-body (WB) integrated single photon emission tomography (SPECT)/computed tomography (CT) in detecting bone metastasis (BM) and to investigate whether WB-SPECT/CT offered any additional benefit value compared to planar bone scintigraphy (PBS) with 99m Tc-hydroxy-methylene diphosphonate or 99m Tc methylene diphosphonate. MATERIALS AND METHODS: Medline, EMBASE, SCOPUS, Web of Science, and CINAHL were searched systematically up to 28 August 2019. All studies using histopathological analysis and/or follow-up imaging and clinical data as the reference standard were eligible for inclusion. RESULTS: Eleven studies (1, 611 patients) were analysed. Based on patient analysis, the sensitivity, specificity, and area under the curve (AUC) of WB-SPECT/CT were 92% (92% confidence interval [CI], 89–95%), 95% (95% CI, 94–96%), and 0.9835, respectively, in the case of negative equivocal findings for BM, and 94% (95% CI, 91–96%), 94% (95% CI, 92–95%), and 0.9790, respectively, when regarded positive. On a lesion basis, these parameters were 91% (95% CI, 89–94%), 96% (95% CI, 94–97%), and 0.9906, respectively, in the case negative equivocal findings, and 92% (95% CI, 89–94%), 95% (95% CI, 94–97%), and 0.9898, respectively, when regarded positive. Comparing 1, 265 patients from eight studies, higher sensitivity (92% versus 74%, p= 0.04) and specificity for WB-SPECT/CT against PBS (93% versus 80%, p= 0.01) in the case of positive equivocal findings; however, when regarded negative, WB-SPECT/CT demonstrated higher sensitivity (91% versus 70%, p= 0.01), but no significant difference was apparent in specificity (94% versus 89%, p= 0.07). CONCLUSION: Compared to PBS, WB-SPECT/CT had superior diagnostic accuracy in BM detection and exhibited a more reliable performance with less equivocal results. Highlights: Whole body-SPECT/CT has superior diagnostic accuracy in bone metastasis detection. Whole body SPECT/CT has better performance than PBS in the detection of BM. Whole body-SPECT/CT has less equivocal outcomes per-patient and lesion analysis. PBS could be replaced by whole body-SPECT/CT in the near future.